Respuesta :

ANSWER:

If [tex]\frac{1}{\sqrt{a}-\sqrt{b}}=\frac{1}{3}[/tex] and [tex]\frac{1}{\sqrt{a}+\sqrt{b}}=\frac{1}{2}[/tex] then the difference of a and b is 6

SOLUTION:

Given, [tex]\frac{1}{\sqrt{a}-\sqrt{b}}=\frac{1}{3}[/tex] →[tex]\sqrt{a}-\sqrt{b}=3[/tex] ----- (1)

And [tex]\frac{1}{\sqrt{a}+\sqrt{b}}=\frac{1}{2}[/tex] → [tex]\sqrt{a}+\sqrt{b}=2[/tex] --- (2)

We have to find difference of a and b.

Now, add (1) and (2)

[tex]\sqrt{a}-\sqrt{b}=3[/tex]

[tex]\sqrt{a}+\sqrt{b}=2[/tex]

Adding above two equations, we get,

[tex]2 \sqrt{a}+0=2+3[/tex]

[tex]\begin{array}{l}{2 \sqrt{a}=5} \\\\ {\sqrt{a}=\frac{5}{2}} \\\\ {a=\frac{25}{4}}\end{array}[/tex]

substitute [tex]\sqrt{a}[/tex] value in (2)

[tex]\begin{array}{l}{\frac{5}{2}+\sqrt{b}=2} \\\\ {\sqrt{b}=\frac{2}{\sin \frac{5}{2}}} \\\\ {\sqrt{b}=\frac{4-5}{2}} \\\\ {\sqrt{b}=\frac{-1}{2}} \\\\ {b=\frac{1}{4}}\end{array}[/tex]

Now, difference of a and b is a – b = [tex]\frac{25}{4}-\frac{1}{4}=\frac{24}{4}=6[/tex]

Hence, the difference of a and b is 6.

ACCESS MORE